11.4k views
1 vote
✖️-101 2 3 f(✖️) -2-1 -1/2-1/4-1/8 -9/4 -7/12 12/7 7/12 Given the following table,fine the rate of change between f(-1) and f(2).

User Shay Guy
by
4.2k points

1 Answer

3 votes

Answer:
(7)/(12).

Explanation:

Given table:

X f(X)

-1 -2

0 -1

1
-(1)/(2)

2
-(1)/(4)

3
-(1)/(8)

i.e. , f(-1) = -2

f(2) =
-(1)/(4)

The rate of change between
f(a) and
f(b)=(f(b)-f(a))/(b-a)

Then, the rate of change between f(-1) and f(2) =
(-(1)/(4)-(-2))/(2-(-1))


=(-(1)/(4)+2)/(3)=((-1+8)/(4))/(3)\\\\=((7)/(4))/(3)\\\\=(7)/(12)

Hence, the rate of change between f(-1) and f(2) is
(7)/(12).

User Siva
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.